Incorporating Gender Dimensions in the Multi-Criteria Management of Homestead Agroforestry in the Kashmir Himalayas - Baksh, Megna Rashid (Indian Journal of Agroforestry, 2026)
Women play a pivotal yet often underrecognized role in sustaining homestead agroforestry systems. Despite their significant contributions, they continue to face systemic barriers, such as wage disparities, limited access to resources, unfavourable working conditions, and the undervaluation of their labour, which is commonly perceived as unskilled and routine. This study aims to integrate gender perspectives into the multi-criteria management of homestead agroforestry in District Anantnag, Jammu & Kashmir. A multi-stage random sampling approach was adopted to select representative villages, blocks, and 171 households (10% sampling intensity). Primary data were gathered through structured, pre-tested interview schedules and non-participant observation, followed by analysis using descriptive and inferential statistics. Results indicated that material benefits of homestead agroforestry, such as fuelwood, food, and fodder, were rated highest by respondents, whereas non-material benefits (environmental and cultural) were considered moderately important. Approximately 70.18% of women independently managed agroforestry activities, and 52.05% were responsible for organising fruit-related inputs. In contrast, male participation in input planning was 29.24%), and joint family involvement was minimal (2.34%). Women performed nearly 70% of operational tasks (weeding, mulching, cleaning, etc.), yet men dominated income-related decision-making (76.02%), with women contributing only 12.28%). Women also exhibited strong leadership in livestock management (91.23%) and household gardening, participating actively in production (67.25%) and harvesting (50.29%). The major constraints identified were small landholdings, long gestation periods, limited technical knowledge, and the complexity of agroforestry systems. Addressing these gender-specific challenges is crucial for enhancing women’s agency, ensuring equitable participation, and strengthening the overall sustainability of homestead agroforestry systems in the region.